1990
DOI: 10.1093/cvr/24.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Acute pulmonary microembolism induces different regional changes in preload and contraction pattern in canine right ventricle

Abstract: Correspondence Letters containing critical assessments of material published in Cardiovascular Research, including reviews, will be considered for publication. They should be sent to the Editor within 6 months of the appearance of the article concerned.Rapid publication Short papers will be considered for rapid publication (within 3 months). These should contain material which merits accelerated publication and must not occupy more than 4 journal pages, including tables, figures and references (authors are res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Greyson et al (11) observed an immediate RV regional dysfunction after brief RV pressure overload. We found out-ofphase beats immediately after PA occlusion, which was similar to the observation of Zwissler et al (36). PA occlusion produced mechanical disturbances within a given region, and among regions in RV.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Greyson et al (11) observed an immediate RV regional dysfunction after brief RV pressure overload. We found out-ofphase beats immediately after PA occlusion, which was similar to the observation of Zwissler et al (36). PA occlusion produced mechanical disturbances within a given region, and among regions in RV.…”
Section: Discussionsupporting
confidence: 91%
“…The different wall motions were enhanced by some interventions. Zwissler et al (36) found out-of-phase movement of inflow and outflow tracts of canine RV after acute pulmonary microembolization. Normalized end-diastolic SL increased in the inflow tract but simultaneously decreased in the outflow tract.…”
Section: Discussionmentioning
confidence: 99%